Development of a Car Accessories Installation Booking System for Toyota Nakornthon Service Center - เติมผล สันติ; ฤทธิ์ไธสง ประไพศรี; บวรรัตนวงศ์ ศิรินญา; ทานา พิพัฒพงศ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of the research were: 1) to develop a car accessories installation booking system for Toyota Nakornthon Service Center, and 2) to evaluate user satisfaction with the developed system. The system was developed as a web application using PHP as the programming language and MySQL as the database management system for data storage. The system development process followed the System Development Life Cycle (SDLC) methodology, including system analysis and design principles. User satisfaction was assessed after system implementation. The sample group was selected using purposive sampling, consisting of 20 participants, including administrators, sale staff, and technical staff of the service center who used and tested the car accessories installation booking system. The research findings revealed that: 1) the developed online car accessories installation booking system was efficient, practically applicable, and effectively supported the service center’s installation booking process in a systematic manner; and 2) overall satisfaction among administrators, sale staff, and technical staff was at a high level, with a mean score of 4.45 and a standard deviation of 0.63. Therefore, the system can effectively support the service operations of Toyota Nakornthon Service Center by improving convenience, speed, reducing work redundancy, and increasing data accuracy.